Friedel–Crafts benzylation of toluene catalyzed by ZnCl2/SiO2 heterogeneous catalyst to para- and ortho-monobenzylated toluene - Iqbal, Anwar; Tan, Kok Hou; Shaari, U. S; Ahmad, Najwa I.N.B.; Adam, Farook; Lee, Hwei Voon; M. Yusop, Rahimi; Abu Bakar, Noor Hana Hanif; Lee, Hooi Ling; Pauzi, Hariy; Abd Malik, Muhammad Fadhirul Izwan; Jusoh, Ahmad Fadly; et al. (Springer Verlag, 2020)
A series of catalysts was prepared for the liquid-phase Friedel–Crafts benzylation of toluene with benzyl chloride (BC) by impregnating rice husk ash silica with ZnCl2 (3 wt%, 6 wt%, 9 wt%, and 12 wt%) via a wet impregnation method. The XRD analysis indicates that the catalysts were amorphous with ill-defined pore systems. The XPS analysis detected the coexistence of ZnO nanoparticles together with ZnCl2 on the catalyst surface, whereas the 29Si NMR analysis indicates the formation of Si–O–Zn bond. Quantitative conversion of benzyl chloride (100%) was achieved within 3 h at 353 K when a catalyst with 9 wt% ZnCl2 was used due to its narrow pore size and high surface area (635 m2 g−1). Para- and ortho-mono-benzylated toluene was obtained as the products. The reaction is proposed to take place via weak attraction between benzyl chloride and the Zn through its chlorine atom. The catalyst was recycled four times with minimum loss (8%) in activity. The benzylation of benzene, toluene, p-xylene, and anisole followed the classical mechanism of Friedel–Craft-type acid-catalyzed benzylation reaction. The BC conversion increased in the order of toluene = p-xylene > anisole > benzene. The catalyst was also screened to be active in the benzoylation of toluene with benzoyl chloride (BOC). The conversion of BOC was 45% with selectivity toward 2-methylbenzophenone (50%) and 3-methylbenzophenone (50%)